Introduction: Social Work Future(s)-What social work does the world need now? - Heather Lynch; Tina Wilson (Social Work & Society, 2023)
This special issue of Social Work & Society includes contributions made to an online conference held in June 2021 that invited speculative engagement with the question What social work does the world need now? The aim of the conference was to create space for uncommon and potentially less intelligible ideas and problematics, and in so doing, foster disciplinary engagement with the possible futures of social work in the context of major societal, environmental and technological changes. To lay out the landscape for the articles that follow, in this editorial, we explore the meaning of the future, as it relates to the trajectory of modernism, through the historical philosophy of Reinhart Koselleck. At this juncture, where existential threats from environmental degradation and new technologies, dominate a zeitgeist of existential angst we question the norms that brought humanity to this point. With scholars from science and philosophy, we conclude that modernism has been destablised, and its norms of human exceptionalism and eternal progress have expired. We argue that in this context, to be of use, social work, a progeny of modernism, must revisit the terms of its relationships and its purpose.